Umana : panorama di vita contemporanea. (Trieste : Edizioni Umana di Aurelia Benco, 1953)
Bibliotheek Camille Huysmans
Periodiciteit: maandelijks
Italiaans
Periodiek
Keywords: cultuur; Venezia Giulia; Italië